The Effect of Teaching Games for Understanding (TGfU) Learning Model on Improving Students’ Social and Cognitive Skills in Physical Education at SMK Merdeka Bandung - Pramudita, Farell Ferdian; Sumpena, Asep; Martini, Tri (Indonesian Journal of Sport Management, 2025)
This study aims to analyze the effect of the Teaching Games for Understanding (TGFU) learning model on improving students' social and cognitive skills in physical education. This study uses a quasi-experimental design with control and experimental groups that were given pre-tests and post-tests. The research sample consisted of 50 students in grade XI at SMK Merdeka Bandung who were randomly selected from existing classes. The experimental group received treatment using the TGFU model, while the control group followed conventional learning. The instruments used to measure social skills were the Social Skills Inventory (SSI), and to measure cognitive skills, the Game Performance Assessment Instrument (GPAI) test was used. The results of data analysis using an independent t-test showed that there were significant differences between the experimental group and the control group on both variables, namely social skills with a significance value of 0.040 and cognitive skills with a significance value of 0.000. These findings indicate that the application of the TGFU model can significantly improve students' social and cognitive skills, so that it can be implemented as an effective approach in physical education learning. Random assignment was carried out within predetermined class boundaries; however, this quasi-experimental design still provides a valid picture of the influence of the TGFU model.